Migration et changement climatique en Amérique Latine : Quels enjeux - Kaenzig Raoul; Piguet Étienne (VertigO)
This literature overview aims to review the relationship between climate change and migration with a special focus on the Latin American continent. After a brief history of the debate raised by the relationship between the environment and migration, we identify the main environmental consequences of climate change. Aspects related to hurricanes, floods, droughts, sea level rise and melting glaciers are most specifically studied. The paper then uses historical analogies : a synthesis of the past migratory consequences of these environmental degradations allows underlining the main migratory issues related to climate change.